Thermostimulated luminescence spectra of InxTl₁-xI nanostructures synthesized in porous silicon - Franiv, A.V.; Bovgyra, O.V.; Savchyn, O.V. (Functional Materials, 2004)
The dose dependence of integral intensity of thermostimulated luminescence spectra of InxTl₁-xI nanostructures synthesized in porous silicon voids and exposed to hard y-radiation has been investigated. The mechanisms of recombination processes and the practical application possibility of the structures obtained as detectors of radioactive irradiation have been discussed. Исследована дозовая зависимость интегральной интенсивности спектров термостимулированной люминесценции нанокристаллов твёрдых растворов замещения InxTl₁-xI, синтезированных в полостях пористого кремния, при у-облучении. Рассматриваются механизмы рекомбинационных процессов и возможность практического использования полученных структур в качестве датчиков радиационного излучения. Досліджєно дозову залежність інтегральної інтєнсивності спєктрів термостимульованої люмінєсцєнції нанокристалів твеpдиx розчинів заміщення InxTl₁-xI, cинтезoваниx у пopoжнинаx пористого кремнію, при у-опроміненні. Розглядаються меxанiзми рекомбі-нацiйниx процесів та можливість практичного застосування oтpиманиx структур як датчиків радіаційного опромінення.